The impact of financial transaction taxes on stock markets: Short-run effects, long-run effects, and reallocation of trading activity - Sebastian Eichfelder; Mona Noack; Felix Noth (Halle Institute for Economic Research (IWH), 2022)
We investigate the impact of the French 2012 financial transaction tax on trading activity, volatility, and price efficiency measured by first-order autocorrelation. We extend empirical research by analysing anticipation and reallocation effects. In addition, we consider measures for long-run volatility and first-order autocorrelation that have not been explored yet. We find robust evidence for anticipation effects before the effective date of the French FTT. Controlling for short-run effects, we only find weak evidence for a long-run reduction of trading activity due to the French FTT. Thus, the main impact of the French FTT on trading activity is short-run. We find stronger reactions of low-liquidity treated stocks and a reallocation of trading activity to high-liquidity stocks participating in the Supplemental Liquidity Provider Programme, which is both in line with liquidity clientele effects. Finally, we find weak evidence for a persistent volatility reduction but no indication for a significant FTT impact on price efficiency measured by first-order autocorrelation.
urn:nbn:de:gbv:3:2-869166
Keywords: G02; G12; H24; M4; 330; anticipation effect; financial transaction tax; long-run treatment effect; market quality; short-run treatment effect